Mitigating disparity?: Treatment patterns, survival, and recurrence rates by race, ethnicity, and hospital site across a large urban health system - Katyayani Papatla; Theofano Orfanelli; Guillaume Stoffels; Tracy Layne; Elena Baldwin; Aurora Leibold; Stephanie V. Blank; Samantha Cohen (Elsevier, 2024)
Objective: National data have shown worse endometrial cancer (EC) outcomes among racial and ethnic minorities. We aimed to analyze EC patient outcomes within a large urban academic health system, with a focus on patterns of care and recurrence rates. Methods: This was a retrospective chart review of EC patients at three system hospitals from 1/1/07-12/31/17. Demographic and clinical factors, including time from EMB to surgery, rate of chemotherapy completion, persistent or recurrent disease, and palliative care referrals were extracted. Descriptive statistics and survival curves were generated. Analysis was done using SAS version 9.4. Results: Black patients had lower overall survival compared to all others on univariate analysis only (p < 0.0001). Hospital site was associated with OS, with the academic anchor and satellite 1 having higher rates of all-cause mortality compared to satellite 2 (HR 4.68 academic anchor, 95 % CI 1.72-12.76, HR 5.36 satellite 1, 95 % CI 1.85-15.52). Time from EMB to surgery and rates of persistent disease following primary treatment were higher in Black patients. After adjusting for stage and grade, chemotherapy completion rate was significantly associated with race. Palliative care was utilized more for Black than White patients after adjusting for stage and grade (p = 0.005). Conclusions: Racial disparities in EC are caused by a complex web of interconnected factors that ultimately lead to worse outcomes in Black women. While precision medicine has helped to close the gap, social determinants of health should be addressed, and models focusing on the complex interactions between biologic, genetic, and social factors should be utilized.